Application Curriculum of Islamic Education Based on Designing Curriculum Management By Paul A. Nelson - Ahmad Halid; Siti Nursyamsiyah; Ahmad Ta’rifin; Saifaldin Idris Onia (Faculty of Education and Teacher Training, Islamic State University of Kiai Haji Achmad Siddiq Jember, 2024)
This research is part of the reaction to the admiration of Paul A Nelson's concept in designing the Education curriculum entitled